Elimination of schistosomiasis transmission in Zanzibar: baseline findings before the onset of a randomized intervention trial. - Stefanie Knopp; Bobbie Person; Shaali M Ame; Khalfan A Mohammed; Said M Ali; I Simba Khamis; Muriel Rabone; Fiona Allan; Anouk Gouvras; Lynsey Blair; Alan Fenwick; Jürg Utzinger; et al. (Public Library of Science (PLoS), 2013)
Gaining and sustaining control of schistosomiasis and, whenever feasible, achieving local elimination are the year 2020 targets set by the World Health Organization. In Zanzibar, various institutions and stakeholders have joined forces to eliminate urogenital schistosomiasis within 5 years. We report baseline findings before the onset of a randomized intervention trial designed to assess the differential impact of community-based praziquantel administration, snail control, and behavior change interventions.In early 2012, a baseline parasitological survey was conducted in ~20,000 people from 90 communities in Unguja and Pemba. Risk factors for schistosomiasis were assessed by administering a questionnaire to adults. In selected communities, local knowledge about schistosomiasis transmission and prevention was determined in focus group discussions and in-depths interviews. Intermediate host snails were collected and examined for shedding of cercariae.The baseline Schistosoma haematobium prevalence in school children and adults was 4.3% (range: 0-19.7%) and 2.7% (range: 0-26.5%) in Unguja, and 8.9% (range: 0-31.8%) and 5.5% (range: 0-23.4%) in Pemba, respectively. Heavy infections were detected in 15.1% and 35.6% of the positive school children in Unguja and Pemba, respectively. Males were at higher risk than females (odds ratio (OR): 1.45; 95% confidence interval (CI): 1.03-2.03). Decreasing adult age (OR: 1.04; CI: 1.02-1.06), being born in Pemba (OR: 1.48; CI: 1.02-2.13) or Tanzania (OR: 2.36; CI: 1.16-4.78), and use of freshwater (OR: 2.15; CI: 1.53-3.03) showed higher odds of infection. Community knowledge about schistosomiasis was low. Only few infected Bulinus snails were found.The relatively low S. haematobium prevalence in Zanzibar is a promising starting point for elimination. However, there is a need to improve community knowledge about disease transmission and prevention. Control measures tailored to the local context, placing particular attention to hot-spot areas, high-risk groups, and individuals, will be necessary if elimination is to be achieved.